The End of the Old France. Book Review of ‘From Triumph to Disaster: Political and Military Defeat of France in 1940 and Its Origins’ by A.A. Vershinin and N.N. Naumova - V. Sergienko-Soler (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The book under review is a new monograph by A.A. Vershinin and N.N. Naumova ‘From triumph to disaster: Political and military defeat of France in 1940 and its origins’, published in 2022. In order to separate myth from reality and restore, as far as possible, an accurate picture of those tragic events, the authors of the monograph under review turn to a wide array of sources — ranging from memoirs of direct participants to archival documents from various countries. They also thoroughly examined the works of both classic and contemporary researches on the military and political history of France. A.A. Vershinin and N.N. Naumova provide an exceptionally detailed picture of the main political, social, military, cultural and ideological reasons that provoked the defeat of the French army. The authors debunk the popular myth that this defeat allegedly resulted from a shortage of military equipment. They show instead that it was caused by a complex of factors: instability of the Third Republic’s regime, contradictions between political parties, strategic miscalculations of the military and politicians. The authors stress that the defeat of France, which allowed the Third Reich to take a dominant position in Europe, became an important milestone in the history of international relations. According to the reviewer, A.A. Vershinin and N.N. Naumova rightly conclude that the old France, which once determined the fate of the world, perished in May-June 1940 in the battles of the Meuse and Dunkirk.